Analysis of Covariance of Cultivation Effect on Body Size/Body Composition/BoneStiffness of Age as Covariate among Residents Living in Hilly Region - KIKKAWA, Kazutoshi (JOURNAL OF THE JAPANESE ASSOCIATION OF RURAL MEDICINE, 2001)
The measurements of body composition of standing body height (HT), body weight (WT), percent body fat (FAT), lean body mass (LBM), and bone stiffness (BONE) by an ultrasound apparatus were performed in 38 male subjects (age range: 19-74 yr) who live in a hilly region. Analysis of variance (ANOVA) and analysis of covariance (ANCOVA) were applied to these anthropometric measurements with the degree of being engaged in agricultural work set as a factor and age of years as a covariate. When each mean value of variables measured in this study were compared to the standard values of the Japanese, the subjects were shorter and lesser in body fat. The correlation coefficients between age and anthropometric measurements of HT, WT, BONE, and LBM except FAT were. The relation between age and BONE showed the upside-down of V letter with the peak at 40 years of age. ANOVA resulted in that the effect of the degree of being engaged in agricultural work was not significant in any anthropometric variable except HT. As a result of ANCOVA, the effect of the degree of being engaged in agricultural work of any variable was not significant except HT. However, the probability of F-value of each variable in ANCOVA became higher than the probability in ANOVA. The significance of F values of ANOVA of BONE, LBM, and WT were lowered after ANOCOVA was applied. The reason is probably then the substantiality of body composition was not enough in the younger generation.